2012
DOI: 10.1128/jcm.06440-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Amphotericin B Resistance in Candida haemulonii and Closely Related Species by Use of the Etest, Vitek-2 Yeast Susceptibility System, and CLSI and EUCAST Broth Microdilution Methods

Abstract: cThe emerging fungal pathogens Candida haemulonii and Candida pseudohaemulonii often show high-level resistance to amphotericin B (AMB). We compared the utilities of five antifungal susceptibility testing methods, i.e., the Etest using Mueller-Hinton agar supplemented with glucose and methylene blue (Etest-MH), the Etest using RPMI agar supplemented with glucose (Etest-RPG), the Vitek-2 yeast susceptibility system, and the Clinical and Laboratory Standards Institute (CLSI) and European Committee on Antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 19 publications
4
37
1
2
Order By: Relevance
“…Notably, the reference CLSI-BMD method in the present series showed reduced AMB MICs in 84% of C. auris isolates. Similarly, low AMB MICs (0.25 to 1 g/ml) by CLSI-BMD were reported for 20 C. auris isolates from South Korea by Shin et al (25). However, these authors observed a high EA (100%) between the CLSI-BMD and Vitek method for AMB, which is in contrast with the observations in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Notably, the reference CLSI-BMD method in the present series showed reduced AMB MICs in 84% of C. auris isolates. Similarly, low AMB MICs (0.25 to 1 g/ml) by CLSI-BMD were reported for 20 C. auris isolates from South Korea by Shin et al (25). However, these authors observed a high EA (100%) between the CLSI-BMD and Vitek method for AMB, which is in contrast with the observations in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…However, these authors observed a high EA (100%) between the CLSI-BMD and Vitek method for AMB, which is in contrast with the observations in the present study. This deviation could be attributed to the low number of isolates tested (25). Major errors of azole susceptibility in 218 isolates of 5 Candida species using another commercial automated reading system (ATB FUNGUS 3) have been reported recently from China, resulting in pseudohigh rates of antifungal resistance (26).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier work, Shin et al. () used 38 species of Candida including 20 C. auris isolates to evaluate the capacity of five phenotypic tests namely, E‐test on Mueller‐Hinton agar supplemented with glucose and methylene blue (E‐test‐MH), E‐test on RPMI agar supplemented with 2% glucose (E‐test‐RPG), Vitek 2, as well as CLSI and EUCAST MBD protocols to determine AMB resistance in vitro. The E‐test‐MH method was adjudged the best in detecting AMB resistance followed by the Vitek 2 among C. haemulonii and C. auris .…”
Section: Diagnostics and Typing Methodsmentioning
confidence: 99%
“…The E‐test‐MH method was adjudged the best in detecting AMB resistance followed by the Vitek 2 among C. haemulonii and C. auris . The CLSI and EUCAST MBD protocols yielded very narrow AMB MICs, which made them unable to efficiently discriminate between AMB susceptible and resistant strains (Shin et al., ). Further tests will be necessary to confirm this preliminary finding.…”
Section: Diagnostics and Typing Methodsmentioning
confidence: 99%
“…So far, the majority of the MIC data for C. auris isolates reported worldwide have been based on the Clinical and Laboratory Standards Institute (CLSI) broth microdilution method, and only a very few, limited to amphotericin B, have been based on the European Committee for Antimicrobial Susceptibility Testing (EUCAST) reference method (16). MICs obtained by the CLSI and EUCAST methods show a good correlation for Candida species and fluconazole and voriconazole in general, whereas MICs obtained by the EUCAST method are typically lower for amphotericin B, anidulafungin, micafungin, and posaconazole (17,18).…”
mentioning
confidence: 99%